102 Cervical cancer screening using primary human papillomavirus (HPV) testing in mozambique: preliminary results of the capulana study. (18th September 2019) - Pontremoli Salcedo, M; Oliveira, C; Andrade, V; Baker, E; Changule, D; Rangeiro, R; Varon, ML; Phoolcharoen, N; Mariano, A; dos Santos, BX; Chalyamba, M; Macaringue, RF; et al.
Abstract : Objectives: Cervical cancer is the leading cause of cancer and related deaths among women in Mozambique. There is limited access to screening and few trained personnel to manage women with abnormal results. Our objective was to implement primary HPV screening in Mozambique and navigate women with abnormal results to appropriate diagnostic and treatment services. Methods: We prospectively enrolled women aged 30 to 49 at Mavalane General Hospital in Maputo, Mozambique. All participants underwent a pelvic examination by a nurse and a cervical sample was collected and tested for HPV DNA using careHPV (Qiagen, Gaithersburg, MD, USA). Women who tested positive for HPV (HPV+) underwent visual assessment for treatment (VAT) using visual inspection with acetic acid (VIA) to assess eligibility for cryotherapy. All HPV+ women were treated with cryotherapy, loop electrosurgical excision procedure (LEEP), or referred for cancer management based on results. Results: From April 2018 to February 2019, 427 women underwent HPV testing. The median age was 39 years. 86/426 patients (20.2%) were HIV positive. 93 patients (21.8%) were HPV+ and 97.8% (91/93) returned for VAT and treatment including cryotherapy (n=68, 74.7%), LEEP (n=10, 11.0%) and referral for cancer management (n=4, 4.4%). Treatment is pending in 9 patients for cryotherapy. Conclusions: Cervical cancer screening with primary HPV DNA testing, including follow-up and treatment, was found to be feasible in Maputo, Mozambique. This study is ongoing to and includes training medical providers to diagnose and treat cervical preinvasive disease and cancer.